Dietary biodiesel-derived crude glycerol in gilthead seabream juveniles (Sparus aurata): effects on growth performance and metabolism - Barbosa, Rita Isabel Pontes (2015)
In the European Union the turn towards renewable energy sources has increased the production of biodiesel from rapeseed oil, leaving glycerol (also known as glycerin) as a valuable by-product. For every litre of biodiesel produced, approximately 79 g of crude glycerol are generated. As the biodiesel production grows, the quantity of crude glycerol generated will be considerable and its utilization will become an urgent topic. One possibility is the use of crude glycerol on animal feeds. Glycerol has been evaluated as a dietary energy source for several farm animals, including fish. A study was undertaken to assess the effect of dietary biodiesel-derived glycerol (from rapeseed oil) on the overall growth performance, digestive capacity and metabolic nutrient utilization in juvenile gilthead seabream fed a low fishmeal level diet. Two practical diets were formulated to be isonitrogenous (crude protein, 45.4% DM), isolipidic (18.5% DM) and isoenergetic (gross energy, 21.3 kJ/g DM). The control diet (CTRL) was formulated with intermediate levels of marine-derived proteins (19%). In the same basal formulation, 5% glycerol (GLY) was incorporated at the expenses of wheat. Each dietary treatment was tested in triplicate tanks over 63 days, with 20 gilthead seabream (Sparus aurata), with a mean initial body weight (IBW) of 27.9  0.12 g. At the end of the trial, fish fed the CTRL diet reached a final body weight of 84.3  2.2 g (more than 3-fold increase of initial body weight). Fish fed the GLY diet showed a significantly higher (P<0.05) growth, expressed in terms of final body weight and specific growth rate. Voluntary feed intake was similar between the two treatments, but both feed efficiency and protein efficiency ratio were significantly improved (P<0.05) in fish fed the GLY diet. Dietary glycerol had no effect (P>0.05) on the apparent digestibility of protein. In comparison to the control treatment, dietary glycerol significantly improved (P<0.05) protein and fat retention. Activities of digestive enzymes were significantly affected by the various dietary treatments. Fish fed the GLY diet showed an enhanced activity of alkaline phosphatase (ALP) and pepsin, while activities of lipase and leucine-alanine peptidase (LAP) were little affected by dietary glycerol. Fish show the ability to use crude glycerol as a dietary energy substrate.